011 Shiftwork, Functional Bowel Symptoms and the Microbiome. (3rd May 2021) - Rogers, Ann; Hu, Yijuan; Yue, Ye; Wessel, Emily; Christie, Jennifer; Read, Timothy
Abstract: Introduction: There are about 15 million Americans working full-time on evening, night, or rotating shifts. Between 48% and 81.9% of those working rotating or night shifts report abdominal pain, constipation, diarrhea and other symptoms of functional bowel disorders. The basis for this high prevalence of functional bowel disorders, including irritable bowel syndrome (IBS), among shift workers is unknown. Animal studies, however, suggest that circadian disruption, similar to that in shift workers, may contribute to the development of GI complaints among shift workers by altering the composition and normal diurnal rhythmicity of the resident intestinal microbes. Methods: Fifty-one full time staff nurses who worked either 12-hour day or night shifts completed demographic information, the Rome III IBS module, daily symptoms diaries for 14 days. They also collected two samples of gut microbiota before the beginning and at the end of their last work shift on day 14, using validated field-tested methods consistent with the Human Microbiome Project. After DNA extraction, 16S rRNA sequencing and assignment to the genus level was completed, samples were then compared to determine if there were 1) differences in the diversity and profile of the microbiome by shift type; 2) if there were differences in the microbiome by time of day for collection; and 3) whether there were differences in the diversity and profile of the microbiome of nurses with IBS and those without IBS. Results: There were no differences in alpha or beta diversity of gut microbiota when specimens from day and night shift nurses were compared. There were however marginal differences in beta diversity when specimens collected at the beginning and end of the shifts were compared, with seven OTUs being differentially abundant when collected from day shift workers in the evening. There were also three OTUs to be differentially abundant in participants reporting IBS symptoms. Conclusion: These data did not reveal strong effects of circadian alterations in gut microbiota related to shiftwork. Other factors, such as insufficient sleep and dietary intake during the data-gathering period, need to be explored Support (if any): Emory University Synergy Grant Program